An analysis of Mindu municipal park on its representativeness for tourism and recreation - Iwata , Maria Jacqueline Ramos; Cemin , Gisele; Teixeira, Maria Adriana Sena Bezerra (Seven Editora, 2023)
Green areas can contribute to the quality of life of the citizen and the urban environment in various ways and are of great importance to the community. In this way, these spaces are references in large urban centers and are more associated with the recreational function, because they offer various types of activities, such as walking, games and relaxation, in addition to working as a point of socialization. The objective of this work was to analyze the activities developed in the Municipal Park of Mindu, its environmental compatibility and to diagnose the potential of tourism. In addition to observing its characteristics, biodiversity, history, attractions, opening hours, main activities and observe the operation of the trails, their potential, possible threats of the existing biome and their importance for tourism and recreation activity. Regarding the methodology, we opted for the qualitative approach of exploratory and descriptive character with direct observation, information was also collected through informal conversations with two employees of the park; news on the website of the Manaus City Hall and local news portals. The results showed that the Mindu Municipal Park is a very popular and ideal place for ecological tourism, recreation, contact with nature and good experiences on paved or dirt trails. The largest flow of people is on weekends for physical activities, yoga, contact with nature and regional breakfast, there are also activities related to sustainability and the environment. It currently has ten tracks; some have the shape of "U" and others that connect with other secondary trails. Points to be improved and suggestions, maintenance of information boards, installation of educational signs about the environment, identification of trees and guided tours in partnership with universities, the creation of a park website to disseminate the activities and other important information, so that the visitor and the tourist record good memories, find signs with adequate information and have autonomy to carry out their activities safely and independently. DOI:https://doi.org/10.56238/alookdevelopv1-042